O direito à memória e o ensino da história do conflito armado colombiano em um ambiente museal - Mojica, July Catalina Torres (2014)
The right to memory is the right that has society to met, remember and find the truth about his own past, especially in situations of recent violence as is the Colombian armed conflict. The right to memory can be granted or denied in the field of history teaching. The history teaching also happens in spaces not schooled as museums. The theme of the research is: how students build historical explanations about the Colombian armed conflict in a museum environment and its relation to the right to memory. The field work develops in the House Museum Jorge Eliecer Gaitan (Bogota-Colombia), with students from the last three grades of the Colombian school system. We start from the assumption that the House Museum Gaitán is linked not only to a painful past, but also to a troubled present. The superimposed temporalities of this museum, are analyzed through the relationships between academic history, school history and common history. For this, converses with the proposed contents for the area of social sciences and the textbook. Ensure a right to memory through the teaching of history, pass to combat official pretensions to impose a single memory of the past, and offer tools so that students can build historical explanations from the critical reasoning. This is possible when students compare different voices that narrate the recent past. In the Colombian case, ensure the right to memory through the teaching of history of recent violence, is even more complex for the role which develops the State itself in the middle of the Colombian internal armed conflict.